Internet Psycho-Education Programs Improve Outcomes in Youth With Type 1 Diabetes - Grey, Margaret (American Diabetes Association, 2013)
OBJECTIVE: The purpose of this study was to determine the efficacy of two Internet-based psycho-educational programs designed to improve outcomes for youth with type 1 diabetes transitioning to adolescence. RESEARCH DESIGN AND METHODS: The study was a multisite clinical trial of 320 youth (aged 11–14 years; 37% minority; 55% female) randomized to one of two Internet-based interventions: TeenCope or Managing Diabetes. Primary outcomes were HbA(1c) and quality of life (QOL). Secondary outcomes included coping, self-efficacy, social competence, self-management, and family conflict. Data were collected at baseline and after 3, 6, and 12 months online. Youth were invited to cross over to the other program after 12 months, and follow-up data were collected at 18 months. Analyses were based on mixed models using intent-to-treat and per-protocol procedures. RESULTS: Youth in both groups had stable QOL and minimal increases in HbA(1c) levels over 12 months, but there were no significant differences between the groups in primary outcomes. After 18 months, youth who completed both programs had lower HbA(1c) (P = 0.04); higher QOL (P = 0.02), social acceptance (P = 0.01), and self-efficacy (P = 0.03) and lower perceived stress (P = 0.02) and diabetes family conflict (P = 0.02) compared with those who completed only one program. CONCLUSIONS: Internet interventions for youth with type 1 diabetes transitioning to adolescence result in improved outcomes, but completion of both programs was better than only one, suggesting that these youth need both diabetes management education and behavioral interventions. Delivering these programs via the Internet represents an efficient way to reach youth and improve outcomes.